PROFESSIONAL DIRECTION OF STUDENTS IN TEACHING ENGLISH - Rasulova, Zukhra (Журнал иностранных языков и лингвистики, 2023)
The article is about organizing innovative methods of teaching professionally oriented English in higher education. The current studies of pedagogical work show that teaching English today is impossible without an innovative component. The main task of the modern type of teaching professionally oriented English is to create methods that integrate interactive approaches to learning and their advantages to solve the main problem of teaching professionally oriented English - foreign language communication in professional situations. The offered material is referred to solve problems in training future professionals by raising their communicative competence in gaining knowledge in English.